Long term transmission expansion planning : a simulated annealing based multiyear algorithm including long term marginal prices - João Paulo Tomé Saraiva (2004)
In this paper we present a multiyear dynamic transmission expansion planning formulation considering criteria related with reliability and investment and operation costs. This problem is solved using an interactive method that starts at a non-dominated solution identified by the -constraint method, in which all objectives except one are converted in constraints using aspiration levels. Afterwards, the decision maker can modify the initial aspiration levels to improve some specific criteria. As a final result, the algorithm determines long term marginal prices, reflecting both investment and operation costs. These prices are well suited to tariff the use of networks as they transmit economic signals to users while addressing the Revenue Reconciliation Problem, typical when using short term approaches. The described approach was used to identify the most adequate 6 year expansion plan for the Portuguese transmission system, the long term marginal prices and the percentage of cost recovery.